Metal–free Decarboxylative Amination: An Alternative Approach Towards Regioselective Synthesis of β‐Carboline N‐fused Imidazoles. Issue 7 (27th January 2017) - Singh, Dharmender; Kumar, Vipin; Devi, Nisha; Malakar, Chandi C.; Shankar, Ravi; Singh, Virender
Abstract: Due to significant activity profile and natural abundance of β‐carboline containing alkaloids, β‐carboline N ‐fused imidazole derivatives were designed and iodine assisted efficient approach was formulated for the regioselective synthesis of designed prototypes via decarboxylative amination of natural α‐amino acids with 1‐formyl pyrido[3, 4‐ b ]indoles. Additionally, oxidative amination with benzyl amines was also investigated for the synthesis of these β‐carboline D‐ring containing frameworks. Abstract :